The Twinning Of Potential: Toward An Integration Of Prior Learning Assessment with Career Development - Peruniak, Geoff; Welch, Deborah (Canadian Journal of Counselling and Psychotherapy, 2007)
This paper argues that prior learning assessment (PLA) is an integral part of the field of career development. Forging closer ties between the two could have a synergistic effect. The authors highlight some common features in the work of practitioners of prior learning assessment and career development. The purpose of this comparison is to emphasize that commonalties of purpose should not be sacrificed to battles of professional identity. A recent project in the Department of Human Resources Development Canada, Alberta/Northwest Territories/Nunavut Region exemplifies benefits and issues associated with the integration of these fields.